1993
DOI: 10.1021/bi00053a001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of protein secondary structure by Fourier transform infrared spectroscopy: A critical assessment

Abstract: The ultimate goal of structural studies of proteins is to gain insight into protein three-dimensional structure at highresolution level. This can often be accomplished by the application of techniques such as X-ray crystallography or multidimensional nuclear magnetic resonance (NMR) spectroscopy. However, high-resolution studies of proteins are not always feasible. For example, crystallographic studies require high-quality single crystals which for many proteins (e.g., the vast majority of membrane proteins) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

46
1,221
0
29

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,503 publications
(1,296 citation statements)
references
References 56 publications
46
1,221
0
29
Order By: Relevance
“…4 Structure-activity studies revealed that peptides containing the highly hydrophobic 25-35 region formed stable aggregates and mediated neuronal death by necrosis or apoptosis. 5,6,7 The truncated A␤ [25][26][27][28][29][30][31][32][33][34][35] fragment includes extracellular and intramembrane residues that have been reported to represent an active region of A␤. 8 In vivo, two nontransgenic rodent models of AD have been studied to analyze the molecular, morphological, and behavioral consequences of amyloid toxicity: the infusion of A␤ 1-40/42 protein and the injection of preaggregated A␤ [25][26][27][28][29][30][31][32][33][34][35] peptide.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…4 Structure-activity studies revealed that peptides containing the highly hydrophobic 25-35 region formed stable aggregates and mediated neuronal death by necrosis or apoptosis. 5,6,7 The truncated A␤ [25][26][27][28][29][30][31][32][33][34][35] fragment includes extracellular and intramembrane residues that have been reported to represent an active region of A␤. 8 In vivo, two nontransgenic rodent models of AD have been studied to analyze the molecular, morphological, and behavioral consequences of amyloid toxicity: the infusion of A␤ 1-40/42 protein and the injection of preaggregated A␤ [25][26][27][28][29][30][31][32][33][34][35] peptide.…”
mentioning
confidence: 99%
“…These models have led to highly pertinent pathomimetic observations and provide complementary approaches to the numerous transgenic mouse lines developed as AD models. In particular, at 1 week after A␤ [25][26][27][28][29][30][31][32][33][34][35] injection, reactive gliosis was observed in the rat hippocampus, 9 caspase-3 activity was induced in the hippocampus and cortex, 9 a reduction in the number of neurons was measured in the CA1 or CA3 hippocampal area, 9 -11 and significant oxidative stress was observed. [11][12][13] Nonetheless, this amyloid toxicity model remains controversial with respect to AD.…”
mentioning
confidence: 99%
See 3 more Smart Citations